2014
DOI: 10.1080/09064702.2014.929168
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the feed intake models in the Nordic feed evaluation system NorFor

Abstract: The objective of this study was to evaluate the feed intake models in the Nordic feed evaluation system NorFor. Data from 196 feeding experiments with dairy cows, and 17 experiments of periodical data, and 135 experiments of complete data with growing cattle were used in the evaluation by mixed model regression. The feed intake by both dairy cows and growing cattle were overestimated by the models. A linear bias indicated that over prediction increased with level of intake both by dairy cows and growing cattle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2015
2015
2016
2016

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 24 publications
(60 reference statements)
0
2
0
Order By: Relevance
“…Accurate predictions of voluntary feed intake are important in the formulation of optimal diets to support the productivity of cows (Allen, 1996). However, evaluations (Krizsan et al, 2014;Jensen et al, 2015a) of the NRC (2001), Zom et al (2012), Gruber et al (2004), TDMI (Huhtanen et al, 2011), and NorFor models showed that these models all had a fairly high prediction error (SD) of 1.5 to 3 kg of DMI/d, and a systematic overprediction at high DMI and underprediction at low DMI. These discrepancies could be due to variable substitution rates between forages and concentrates depending on the energy balance and intake (Faverdin et al, 1991(Faverdin et al, , 2011.…”
Section: Introductionmentioning
confidence: 99%
“…Accurate predictions of voluntary feed intake are important in the formulation of optimal diets to support the productivity of cows (Allen, 1996). However, evaluations (Krizsan et al, 2014;Jensen et al, 2015a) of the NRC (2001), Zom et al (2012), Gruber et al (2004), TDMI (Huhtanen et al, 2011), and NorFor models showed that these models all had a fairly high prediction error (SD) of 1.5 to 3 kg of DMI/d, and a systematic overprediction at high DMI and underprediction at low DMI. These discrepancies could be due to variable substitution rates between forages and concentrates depending on the energy balance and intake (Faverdin et al, 1991(Faverdin et al, , 2011.…”
Section: Introductionmentioning
confidence: 99%
“…The fit of the models were evaluated from the root-mean-square error (RMSE), from Akaike's information criterion (AIC), and from the significance of regression parameters. The smaller the RMSE and AIC are, the stronger the relationship of the residuals to the variables examined is (Krizsan et al, 2014).…”
Section: Mef=1mentioning
confidence: 99%